An "on-off" ratio photoluminescence sensor based on catalytically induced PET effect by Fe3O4 NPs for the determination of coumarin. (30th January 2022) - Yang, Wei; Weng, Chenyuan; Li, Xiaoyun; Xu, Wei; Fei, Jianwen; Hong, Junli; Zhang, Jun; Zhu, Wanying; Zhou, Xuemin
Highlights: Construct a coumarin ratio fluorescence sensor with artificial nano enzymes firstly. Fe3 O4 NPs used to conveniently control the catalytic reaction and purification system. The method for analysis of complex samples with great selectivity and sensitivity. Abstract: Herein, using Fe3 O4 nanoparticles (Fe3 O4 NPs) as a magnetic artificial peroxidase, an "on–off" ratiometric photoluminescence sensor with high-sensitivity and high-selectivity for coumarin was constructed based on photoinduced electron transfer (PET) between 7-hydroxycoumarin and rhodamine B (RB). The results showed that Fe3 O4 NPs catalyzed H2 O2 to generate nucleophilic group ·OH, which attacked the active site of coumarin and produced strong fluorescent 7-hydroxycoumarin molecules. Then, the fluorescence of RB was quenched with 7-hydroxycoumarin through the PET effect. The ratio signal generated in the above process was used for the quantitative detection of coumarin. Under optimized conditions, the linear range 0.5–25 mg/L was acquired for coumarin with the detection limit of 0.016 mg/L. This method had excellent selectivity and the recovery rate was 81.8%−106.8% with the relative standard deviation less than 5.6%, so it can be used for the quantitative analysis of coumarin in complex matrix samples.